Acolhimento no banco de leite humano: construção participativa de tecnologia educacional fundamentada no Arco de Maguerez - Bianca Maria Innocencio da Silveira Lobo; Elaine Antunes Cortez; Claudia Maria Messias; Melissa Rangel Paulista; Camilly Cardoso da Silva; Rebeca Grassini Gomes de Carvalho (Online Brazilian Journal of Nursing, 2026)
Objective: To analyze the reception at the Human Milk Bank (HMB) and develop a participatory and educational technology focused on Permanent Education in Health (PEH), to favor the reception of lactating women. Method: Participatory qualitative research, based on the Maguerez Arch, conducted with 22 participants (11 lactating women and 11 health professionals) at a university hospital in Niterói, RJ. The methodological path followed five stages: 1) Observation of reality (participant observation and questionnaires for lactating women); 2) Identification of key points; 3) Theorization (based on Merhy's framework and PEH policy); 4) Solution hypotheses (development and collective validation of an educational video); and 5) Application to reality (dissemination and registration of the technology). Results: Immersion revealed quality of care and technical excellence, but also emotional vulnerabilities (27.27% at risk of postpartum depression) and gaps. These data served as reflective triggers in the workshops, resulting in thematic categories regarding reception challenges. The synthesis culminated in the creation of an educational video to sensitize the team regarding subjective and integral support for women. Conclusion: The study fulfilled its objective by producing the video as a PEH technology. The tool proved capable of mediating reflections on "living work in act," enhancing reception and the humanization of practices at the Milk Bank.